B-Type Natriuretic Peptide in Bronchiolitis: Its Relationship with Left Ventricular Systolic Functions and Prognosis - Gülşen Kes; Gülser Esen Besli; Yusuf İzzet Ayhan; Nurdan Erol; Ferruh Kemal İşman (Galenos Yayinevi, 2018)
Introduction:We have limited information about the clinical importance of plasma B-type natriuretic peptide (BNP) level and its prognostic value in children with bronchiolitis. In this study, we aimed to determine basal plasma BNP levels and their relationship with left ventricular systolic functions and prognosis in patients hospitalized with moderate to severe bronchiolitis.Methods:The study was conducted prospectively on 37 patients aged 1-24 months with a modified Wang respiratory score of 6 and above and diagnosed with bronchiolitis. The patients with high (>100 pg/mL, n=6) and normal (≤100 pg/mL, n=31) serum BNP levels were compared in terms of left ventricular systolic functions, and vital, laboratory, and radiological findings. The relationship between serum BNP level and prognosis was evaluated.Results:The mean basal plasma BNP level in the patients was significantly higher than in controls (61.75±65 pg/mL vs. 13.99±8.79 pg/mL; p=0.001). There was no significant difference in ejection fraction and fractional shortening values between the patients with normal and high BNP levels and controls (p>0.05). Patients with high BNP levels had higher mean partial carbon dioxide values than patients with normal BNP levels (p=0.037). There was a positive correlation between plasma BNP level and length of hospital stay (r=0.286; p=0.007) and intensive care unit stay (r=0.645; p=0.000).Conclusion:An increase in serum BNP levels may be seen in patients with moderate to severe bronchiolitis without myocardial dysfunction. It was argued that this BNP increase may be related to the degree of deterioration of gas exchange associated with the disease. Plasma BNP level is a potential prognostic factor in moderate to severe bronchiolitis.